Income Tax Issues on the Omnibus Law and Its Implications in Indonesia - Saptono, Prianto Budi; Ayudia, Cyntia (AKRUAL: JURNAL AKUNTANSI, 2021)
This research has two objectives. The first objective is to analyze the issue of income tax policy based on the idea of taxation omnibus law. In 2020, Law No. 36 of 2008 concerning Income Tax was amended twice as stipulated in Law No. 2 of 2020 and Law No. 11 of 2020 (Job Creation Law). The second objective is to analyze the implications of income tax policy changes on taxation practices in Indonesia. This research is a descriptive qualitative study using data collection techniques in documentation and literature studies. The research concludes that the omnibus law policy aims to encourage domestic investment funding. Income tax issues in Law No. 2 of 2020 include lowering the corporate income tax rate and imposing taxes on trade through an electronic system. Besides, the issue of income tax in Law No. 11 of 2020 includes tax subjects' determination, the territorial system's adoption, tax objects' exclusion, and changes to the provisions on dividends. The implication of the change in income tax policy on taxation practices is that taxes distort the economy. The delegation of regulations for reducing income tax rates to the government through government regulations creates legal uncertainty. Thus, it is necessary to have tax regulations with minimal complexity, not overlap, provide legal certainty, and further encourage voluntary tax compliance.